Dinge sammeln, Wissen schaffen : Die Geschichte der naturhistorischen Sammlungen in Basel, 1735-1850 - Häner, Flavio (2017)
From how the mammoth came to the museum to how scientific facts emerged from the collected artifacts - a history of scientific collections.